Knowledge, attitude and practices concerning Hepatitis B infection, among healthcare workers in Bantama, Ghana: a cross sectional study - Afihene, Mary Y.; Duduyemi, Babatunde M.; A-Tetteh, Hannah-Lisa; Khatib, Mahafroz (International Journal Of Community Medicine And Public Health, 2017)
Background: Hepatitis B is a serious, global, public health problem that gives rise to hepatocellular carcinoma / liver cancer with a mortality rate of about 600000 people, worldwide. Despite increasing prevalence of HBV and health care workers (HCWs) being at high risk for HBV, there is paucity of information on knowledge, attitude and practice (KAP) concerning HBV among HCWs, especially among developing countries like Ghana. Improved HBV related knowledge is imperative for developing an informed positive environment which can import, support and maintain HVB control good practices. Methods: This quantitative cross-sectional study aimed to evaluate KAP of HCWs was undertaken amongst 175 HCWs of Suntreso Government Hospital, Ghana. KAP regarding HBV were assessed using a standardized structured questionnaire. Descriptive statistics for patients’ demographic characteristics and mean scores for knowledge, attitude and practice of HCWs were applied. To establish association between study variables, Kruskal Wallis test and to assess the association between the KAP scores, Spearman’s rho correlation were used. Results: Mean scores for KAP were 13.691±2.81, 6.685±2.28 and 2.23±1.19 respectively. Age, occupation and experience were significantly associated with mean knowledge scores (p<0.05). Spearman rank correlation revealed significant positive correlations between knowledge-attitude (r = 0.539, p < 0.01), knowledge-practice (r = 0.388, p < 0.01) and attitude-practice (r = 0.458, p < 0.01). Conclusions: The study highlighted non-optimal KAP with regards to several aspects of HBV. Hence, there arises a need for policy guidelines along with extensive health education campaigns to manage all aspects of KAP of HCWs regarding HBV.